Forensic timber identification: It's time to integrate disciplines to combat illegal logging. (November 2015) - Dormontt, Eleanor E.; Boner, Markus; Braun, Birgit; Breulmann, Gerhard; Degen, Bernd; Espinoza, Edgard; Gardner, Shelley; Guillery, Phil; Hermanson, John C.; Koch, Gerald; Lee, Soon Leong; Kanashiro, Milton; et al.
Abstract: The prosecution of illegal logging crimes is hampered by a lack of available forensic timber identification tools, both for screening of suspect material and definitive identification of illegally sourced wood. Reputable timber traders are also struggling to police their own supply chains and comply with the growing requirement for due diligence with respect to timber origins and legality. A range of scientific methods have been developed independently with the potential to provide the required identification information, but little attention has been given to how these tools can be applied synergistically to support the legal timber trade. Here we review the use of visual identification methods (wood anatomy, dendrochronology), chemical methods (mass spectrometry, near infrared spectroscopy, stable isotopes, radio-carbon), and genetic methods (DNA barcoding, population genetics/phylogeography, DNA fingerprinting) each with potential application to forensic timber identification. We further highlight where future research and development are required to identify illegal logging crimes using these methods and suggest ways in which multiple methods can be used together to answer specific identification questions. We argue that a new integrated field of forensic timber identification should be a global investment priority, for which the ongoing collection, curation and taxonomic study of appropriate reference material is a critical part. Consideration of the specific legal requirements for method development and the application of identification methodologies to criminal evidence are also imperative to achieve robust scientific support for illegal logging crime prosecutions and prevention. Highlights: Prosecution of illegal logging crimes is hampered by lack of forensic timber identification tools. A range of visual, chemical and genetic identification methods have been developed independently We review the use of these methods and highlight future research and development needs. We explore how multiple methods can be used together to answer specific identification questions. We call for the new integrated field of forensic timber identification to be a global investment priority.